Undiagnosed Abdominal Term Pregnancy with Good Neonatal Outcome - Phoy Cheng Chun; Ka-Hee Chua; Mohamed Siraj Shahul Hameed; Manisha Mathur; Wai Kheong Ryan Lee (Case Reports in Obstetrics and Gynecology)
Abdominal pregnancy is a rare occurrence and it represents only 1% of ectopic pregnancy. We report a case of an abdominal pregnancy that resulted in a term live baby. Diagnosis is unsurprisingly difficult in advanced gestation. A high index of suspicion detailed clinical and imaging examinations are needed to make the diagnosis. Multidisciplinary team involvement is crucial in the management of abdominal pregnancy.